Position statement of the hereditary angioedema Section of the Polish Society of Allergology on the management of hereditary angioedema due to C1 inhibitor deficiency: 2025 update. Part I: Classification, pathophysiology, clinical presentation, diagnosis, and differential diagnosis - Porębski, Grzegorz; Kucharczyk, Aleksandra; Matuszewski, Tomasz; Danielewicz, Hanna; Gocki, Jacek; Grzela, Katarzyna; Juchacz, Aldona; Kurowski, Marcin; Kuziemski, Krzysztof; Łukaszyk, Mateusz; Sokołowska, Małgorzata; Stobiecki, Marcin; et al. (Alergologia Polska - Polish Journal of Allergology, 2025)
Hereditary angioedema due to a genetically determined deficiency of the C1 complement inhibitor (HAE-C1INH) is a rare disease that significantly impairs daily functioning and may be life-threatening in severe cases. Angioedema attacks are triggered by a transient, localized increase in bradykinin levels and may affect the skin as well as the mucous membranes lining the gastrointestinal and respiratory tracts. The first recommendations of the Polish expert group on HAE-C1INH were published in 2018. The dynamic advancement of medical knowledge and the emergence of new therapeutic options created a strong need to revise and update these recommendations. This updated position statement by the HAE Section of the Polish Society of Allergology is based on the latest medical evidence on HAE-C1INH and takes into account local healthcare conditions. Part I of the document addresses clinical presentation, pathophysiology, diagnostic criteria, differential diagnosis, and the classification of HAE-C1INH within the current angioedema classification system.